Konstruksi Literasi Digital Pengguna Media Sosial dalam Mencegah Penyebaran Berita Hoaks di Kalangan Mahasiswa UINSU - Darni Angkat; Anang Anas Azhar (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The proliferation of hoax news on social media has become a serious challenge in digital communication, as it can distort public understanding of information and shape erroneous public opinion. Digital literacy therefore stands as an indispensable competence for social media users to critically evaluate and respond to information circulating in digital spaces. This study aims to analyze the construction of digital literacy among social media users in preventing the spread of hoax news among students of the Communication Science Program, Faculty of Social Sciences, Universitas Islam Negeri Sumatera Utara (UINSU). A qualitative approach with a descriptive research design was applied. Informants were selected through purposive sampling. Data were gathered through in-depth interviews, observation, and documentation, while data analysis followed the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings indicate that students' digital literacy is constructed through media experience, social interaction, and their academic background in communication studies. At the same time, the practice of digital literacy encounters obstacles such as the rapid circulation of information on social media, reliance on particular sources, and habitual information sharing within digital social networks. This study further demonstrates that digital literacy is not solely an individual capacity, but also a process of social construction within the dynamics of digital communication